Modulation of Chaos with Optoelectronic Feedback in Semiconductor Laser - Adnan , Maha N.; Al Naimee, Kais A. (Iraqi Journal of Science, 2022)
The modulation of chaotic behavior in semiconductor laser with A.C coupling optoelectronic feedback has been numerically and experimentally reported. The experimental and numerical studying for the evaluation of chaos modulation behavior are considered in two conditions, the first condition, when the frequency of the external perturbation is varied, secondly, when the amplitude of this perturbation is changed. This dynamics of the laser output are analyzed by time series, FFT and bifurcation diagram.